Recovery of deproteinised small rubber particles from skim natural rubber latex: effect of some inorganic salts - Sakdapipanich J T; Nawamawati K; Tanaka Y (Journal of Rubber Research, 2002)
Phase separation of cream skim natural rubber (NR) latex containing small rubber particles of about 0.1 Mm was observed by the addition of inorganic salt into fresh skim latex or deproteinised skim latex. Cream skim latex was obtained by centrifugal separation of the resulting cream phase with high yield and purity by the addition of inorganic salts with protease or deproteinised skim latex. The skim rubber from deproteinised skim rubber contained less than 0.02;nitrogen content.
Keywords: Centrifugation; Deproteinised skim latex; Inorganic salt; NR latex; Protease; Small rubber particles